Antimicrobial-Resistant Escherichia coli in Public Beach Waters in Quebec. Issue 2 (2012) - Turgeon, Patricia; Michel, Pascal; Levallois, Patrick; Chevalier, Pierre; Daignault, Danielle; Crago, Bryanne; Irwin, Rebecca; McEwen, Scott A; Neumann, Norman F; Louie, Marie
Abstract : INTRODUCTION: Human exposure to antimicrobial-resistant bacteria may result in the transfer of resistance to commensal or pathogenic microbes present in the gastrointestinal tract, which may lead to severe health consequences and difficulties in treatment of future bacterial infections. It was hypothesized that the recreational waters from beaches represent a source of antimicrobial-resistant Escherichia coli for people engaging in water activities. OBJECTIVE: To describe the occurrence of antimicrobial-resistant E coli in the recreational waters of beaches in southern Quebec. METHODS: Sampling occurred over two summers; in 2004, 674 water samples were taken from 201 beaches, and in 2005, 628 water samples were taken from 177 beaches. The minimum inhibitory concentrations of the antimicrobial-resistant E coli isolates against a panel of 16 antimicrobials were determined using microbroth dilution. RESULTS: For 2004 and 2005, respectively, 28% and 38% of beaches sampled had at least one water sample contaminated by E coli resistant to one or more antimicrobials, and more than 10% of the resistant isolates were resistant to at least one antimicrobial of clinical importance for human medicine. The three antimicrobials with the highest frequency of resistance were tetracycline, ampicillin and sulfamethoxazole. DISCUSSION: The recreational waters of these beaches represent a potential source of antimicrobial-resistant bacteria for people engaging in water activities. Investigations relating the significance of these findings to public health should be pursued.